2016
DOI: 10.1103/physrevd.93.073008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of nuclear effects in the interpretation of the MiniBooNE low-energy anomaly

Abstract: 13 pagesInternational audienceWe study the impact of the effect of multinucleon interactions in the reconstruction of the neutrino energy on the fit of the MiniBooNE data in terms of neutrino oscillations. We obtain some improvement of the fit of the MiniBooNE low-energy excess in the framework of two-neutrino oscillations and a shift of the allowed region in the $\sin^2 2\vartheta$--$\Delta{m}^2$ plane towards smaller values of $\sin^2 2\vartheta$ and larger values of $\Delta{m}^2$. However this effect is not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 196 publications
(257 reference statements)
1
24
0
Order By: Relevance
“…There are few remarks about this conclusion. First of all, this analysis has been performed by considering the multinucleon contributions as calculated Another example of neutrino oscillation analysis which quantitatively takes into account the effects of the multinucleon emission channel is the one performed by Ericson et al [381] in the context of the MiniBooNE ν µ → ν e low energy anomaly [54,55], related to the possible existence of sterile neutrinos. Ericson et al shown that taking into account the multinucleon effects in the analysis of MiniBooNE data allows a slightly better fit of the MiniBooNE low-energy excess and induces a shift of the allowed region in the sin 2 2ϑ -∆m 2 plane towards smaller values of sin 2 2ϑ and larger values of ∆m 2 in the framework of twoneutrino oscillations.…”
Section: Neutrino Energy Recostruction and Neutrino Oscillation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There are few remarks about this conclusion. First of all, this analysis has been performed by considering the multinucleon contributions as calculated Another example of neutrino oscillation analysis which quantitatively takes into account the effects of the multinucleon emission channel is the one performed by Ericson et al [381] in the context of the MiniBooNE ν µ → ν e low energy anomaly [54,55], related to the possible existence of sterile neutrinos. Ericson et al shown that taking into account the multinucleon effects in the analysis of MiniBooNE data allows a slightly better fit of the MiniBooNE low-energy excess and induces a shift of the allowed region in the sin 2 2ϑ -∆m 2 plane towards smaller values of sin 2 2ϑ and larger values of ∆m 2 in the framework of twoneutrino oscillations.…”
Section: Neutrino Energy Recostruction and Neutrino Oscillation Analysismentioning
confidence: 99%
“…In Ref. [381] Ericson et al also performed a global fit of short-baseline neutrino oscillation data in the framework of 3+1 neutrino mixing showing that taking into account the multinucleon interactions in the analysis of MiniBooNE data lead to a decrease of the appearance-disappearance tension. However, this effect is not enough to solve the problem of the appearance-disappearance tension in the global fit of short-baseline neutrino oscillation data, because the value of the appearance-disappearance parameter goodness-of-fit is still too small.…”
Section: Neutrino Energy Recostruction and Neutrino Oscillation Analysismentioning
confidence: 99%
“…Part of the MiniBooNE low-energy anomaly may be explained by taking into account nuclear effects in the energy reconstruction[151,152], but this effect is not sufficient to solve the problem[153].…”
mentioning
confidence: 99%
“…We considered the space of the two parameters ∆m 2 41 m 2 4 and sin 2 2ϑ ee = 4|U e4 | 2 (1− |U e4 | 2 ) in order to compare the sensitivity of 163 Ho experiments with the results of global analyses of short-baseline neutrino oscillation data [18,22,55,[120][121][122][123][124][125][126][127][128][129]. We calculated the sensitivity of 163 Ho experiments in the sin 2 2ϑ ee -∆m 2 41 plane with a method similar to that described in section 4, using the spectrum in eq.…”
Section: +1 Neutrino Mixingmentioning
confidence: 99%